Preliminary analysis of the antinociceptive activity of zerumbone - Sulaiman, Mohd Roslan; Perimal, Enoch Kumar; Zakaria, Zainul Amiruddin; Mokhtar, Fuzi; Akhtar, Muhammad Nadim; Lajis, Md Nordin; Israf Ali, Daud Ahmad (Elsevier, 2009)
We have investigated the antinociceptive activity of zerumbone (1), a natural cyclic sesquiterpene isolated from Zingiber zerumbet Smith, in acetic acid-induced abdominal writhing test and hot plate test in mice. 1 given by intraperitoneal route produced significant dose-dependent antinociceptive effect in all the test models used. In addition, the antinociceptive effect of 1 in the hot plate test was reversed by the non-selective opioid receptor antagonist naloxone, suggesting that the opioid system is involved in its analgesic mechanism of action.